Polyphonie et hantise dans Villette : quelques aspects du pacte de lecture - Isabelle Hervouet-Farrar (Cahiers Victoriens et Edouardiens)
Narration in Villette relies heavily on the figure of Lucy’s narratee, whom she addresses as often as fifty-three times in the course of the novel. This paper reconsiders the narrator-narratee contract in Villette and shows how the narratee’s rational presence turns dialogism into an essential feature of this very unusual fictional autobiography; and contributes to the creation of a truly subversive and original piece of fiction. Dialogism however also bears witness to Lucy’s uneasy writing of experience. As early as the first three chapters (based on Paulina’s uncanny apparition at Bretton), the names of characters and places in Villette appear as cryptonyms pointing to an ever-present ghostly figure, the absent mother, a threat to the female subject’s autonomy. One possible conclusion is that Lucy wishes her narratee to be rational in order to help her escape the threat of psychic annihilation.